Demands for access to new therapies: are there alternatives to accelerated access?. (2nd October 2017) - Pace, Jessica; Ghinea, Narcyz; Kerridge, Ian; Lipworth, Wendy
Abstract : Patients deserve timely access to new therapies, but the rhetoric surrounding accelerated access impedes rational policy making, argue Jessica Pace and colleagues